Research on static characteristics of elastic foil gas thrust bearing applied to aeronautical ACM. Issue 1 (1st May 2022) - Song, Chao; Bian, Zhi; Du, Jianjun; Ding, Shunan; Zhu, Jianjun
Abstract: In air conditioning system for aircraft, air cycle machine (ACM) is the flimsy core component, which is impacted observably by the performance and reliability of elastic foil air-dynamic pressure bearing. It's necessary to have research on static characteristics of elastic foil air-dynamic pressure bearing. Based on finite element analysis (FEA) theory, it's clearly obtained that discretized fluid lubrication Reynolds equation of foil dynamic pressure bearing by the weighted residual method. Coupled with the elastic deformation of foil calculated by beam element model, foil gas film thickness equation is used to work out static characteristics of elastic foil air-dynamic pressure bearing by iterative calculation. And then, it's known how the basic parameters of the bearing impact its static characteristics. The result of the method in this paper, is verified that it's correct by the experiment data in other relevant papers, and it's appropriate to be used as guidance and reference for the further application of elastic foil bearing in ACM.